Birds in Dictionary of the Khazars by Milorad Pavić - Marićević Balać, Jelena Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The research of birds in the novel Dictionary of the Khazars begins with the comparison of the understanding of the bird universe in the poetry of Đorđe Marković Koder, and continues with the analysis of the symbolism and the function of 29 bird species mentioned in the novel. Bird species can be divided into two basic groups which include both positively and negatively connoted birds. The aim of the paper is to determine the origin of the bird symbolism in the novel and to attempt to typologize the ornithological universe of the novel. Birds who convey a positive meaning include: a) those thanks to which memory, reproduction, and the knowledge of language, the poetry of the original dictionary of the Khazars is preserved from oblivion (the parrot, the starling, the swallow, the albatross); b) birds which, as interpreters, aid the reading methods or symbolize divine or mystical knowledge (the jay, the kestrel, the pigeon, the heron, the eagle); c) symbols of spiritual values, healing, salvation, and resurrection (the “ku,” the pigeon, the ostrich, the falcon, the chaffinch, the goose, the chicken, the barn owl). On the other side are the following birds: a) symbols of death (the hawk, the sparrow hawk, the cuckoo, the tit, the woodpecker, the crow); b) birds of the underworld, demonic and of the devil (the crow, the jackdaw, the partridge, the woodcock); c) birds that signify nothingness (the mallard, the duck, the swan, the collared dove, the swift).